2012
DOI: 10.1124/mol.111.076604
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Transcript Diversity Creates New Opportunities for Pharmacological Intervention

Abstract: Most protein coding genes generate multiple RNA transcripts through alternative splicing, variable 3Ј and 5ЈUTRs, and RNA editing. Although drug design typically targets the main transcript, alternative transcripts can have profound physiological effects, encoding proteins with distinct functions or regulatory properties. Formation of these alternative transcripts is tissueselective and context-dependent, creating opportunities for more effective and targeted therapies with reduced adverse effects. Moreover, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 131 publications
(120 reference statements)
1
28
0
Order By: Relevance
“…RNA editing is recognized as a potential target for drug discovery at different diseases, but, so far, few studies have been reported [72]. Therapies that correct aberrant splicing of mRNA transcripts using splice-site-directed oligonucleotides are being tested in clinical trials of genetic disorders such as Duchenne muscular dystrophy [73].…”
Section: Glutamate Receptors As Targets For Therapeutic Drug Developmentmentioning
confidence: 99%
“…RNA editing is recognized as a potential target for drug discovery at different diseases, but, so far, few studies have been reported [72]. Therapies that correct aberrant splicing of mRNA transcripts using splice-site-directed oligonucleotides are being tested in clinical trials of genetic disorders such as Duchenne muscular dystrophy [73].…”
Section: Glutamate Receptors As Targets For Therapeutic Drug Developmentmentioning
confidence: 99%
“…In the UK, the Ancestry and Biological Informative Markers for Stratification of Hypertension (AIM HY) study 102 will investigate pharmacogenomic and pharmacometabolomic signatures of antihypertensive drug response, and use this information to prospectively identify and test a personalized antihypertensive treatment approach. Lastly, transcriptomics — the study of the complete set of RNA transcripts that are produced by the genome — is another ‘omics’ approach that could be useful to elucidate drug response mechanisms 103 . Tools for studying genome-wide microRNAs that may affect expression, methylation, and other genetic modifiers are also gaining interest.…”
Section: Future Directionsmentioning
confidence: 99%
“…This suggested that unknown GABAB1 splicing variants are differentially expressed in alcoholic brain. Single nucleotide polymorphisms (SNPs) near splicing sites also alter splicing and may be associated with alcoholism (11-13). Chronic ethanol exposure and withdrawal increased 5’ splice variant expression of the N-Methyl-D-aspartic acid receptor subunit, NR1, without NR1 3’ variant expression changes (14).…”
Section: Introductionmentioning
confidence: 99%